Pulsating flow and heat transfer of power-law fluid in a circular pipe - Altunkaya, Ayse Nur; Aydin, Orhan; Avci, Mete (Nonlinear Analysis: Modelling and Control, 2022)
In this study, the pulsating flow of a non-Newtonian fluid and heat transfer in a pipe with uniform heat flux at its wall is examined analytically. The flow is assumed to be both hydrodynamically and thermally fully developed. The perturbation method based on the series expansion is used in the analysis. The periodic change and period-averaged values of the friction factor and Nusselt number as well as velocity and temperature profiles are obtained at varying values of dimensionless frequency and amplitude for shear-thinning, Newtonian and shear-thickening fluids. It is shown that the frequency is effective on the friction factor for a specific range of the dimensionless frequency. For some specific cases, excellent agreements are obtained with the literature. It is disclosed that the dimensionless frequency, the amplitude and the power-law index are interactively effective on the friction and heat transfer.
Keywords: pulsating flow; pipe; power-law fluid; heat transfer